Synthesis of mesoporous nanoparticles via microwaveassisted method for photocatalytic degradation of phenol derivatives - Nur Farhana, Jaafar; Nor Amira, Marfur; Nurfatehah Wahyuny, Che Jusoh; Nagao, Yuki; Nur Hidayahtul Nazirah, Kamarudin; Rohayu, Jusoh; Mohammad Anwar, Mohamed Iqbal (Universiti Kebangsaan Malaysia, 2019)
Mesoporous transition metal oxides have gained attention widely since they possess both optical and electronic properties of transition metal oxides especially for photocatalytic degradation application. In this research work, mesoporous titania nanoparticles (MTN) and mesoporous zinc oxide nanoparticles (MZN) were successfully synthesized using microwave (MW)- assisted method to degrade phenol derivatives under visible light irradiation. The microwave sintering effect on the surface of these modified structures was studied to relate with their photocatalytic performance. The characterization results indicated that MW-assisted method was mainly contributed in generating Ti3+ site defects (TSD) and oxygen vacancies (OV) in MTN while for MZN contained only OV as one of the strategies in light-absorption modification for TiO2 and ZnO to enhance their photoactivity. MTN also showed the degradation of 2-chlorophenol was up to 97% while degradation of phenol by MZN was up to 87%.